Analisis Kebijakan Sistem Zonasi di Tengah Ketimpangan Kualitas Pendidikan Nasional - Fiddini, Putri Fahma; Salsabila, Fadilah; Latif, Muaziz (Lembaga Yasin AlSys, 2023)
Inequalities in the quality of education still occur in several regions in Indonesia, where there is still a clear gap in the quality of education. One effort to improve and evenly distribute the quality of education in Indonesia is by applying the zoning system to the process of accepting new students. The provisions of the zoning system are contained in Permendikbud No. 14 of 2018. This study aims to analyze educational policies relating to the zoning system in the acceptance of new students. The research method used in this research is a qualitative method with the type of descriptive research approach to the study of documents / texts.